Evaluation of the Integration of Learning Management Systems with Virtual Reality Platform - Farameita, Era; Kurniasari, Florentina; Tjahjana, David (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study evaluates the integration of Virtual Reality (VR) into Learning Management Systems (LMS) and its impact on learner engagement, motivation, and retention within a professional training context. Employing a mixed-methods design, data were collected from 200 participants using pre- and post-tests, system-generated metrics, questionnaires based on Self-Determination Theory (SDT), and qualitative interviews. Quantitative analyses, including descriptive statistics, Pearson correlation, t-tests, ANOVA, and multiple regression, revealed that VR usage significantly enhanced learning outcomes, with VR exposure time and perceived learner autonomy emerging as key predictors of retention. Younger and male participants demonstrated higher retention scores, highlighting the moderating effect of age and gender. Qualitative findings supported the quantitative results, indicating increased immersion and conceptual understanding despite minor technical challenges. Confirmatory Factor Analysis (CFA) confirmed the validity and reliability of the measurement instruments. These findings provide empirical support for the pedagogical potential of VR-integrated LMS environments and offer practical recommendations for personalized instructional design in digital education.